Gut Microbiota and Serum Metabolite Potential Interactions in Growing Layer Hens Exposed to High-Ambient Temperature - Zhou, Changming; Gao, Xiaona; Cao, Xianhong; Tian, Guanming; Huang, Cheng; Guo, Lianying; Zhao, Yulan; Hu, Guoliang; Liu, Ping; Guo, Xiaoquan (Frontiers in Nutrition, 2022)
Emerging evidence has revealed the dysbiosis of gut microbiota contributes to development of metabolic diseases in animals. However, the potential interaction between gut microbiota and host metabolism in growing hens under metabolic disorder induced by chronic heat exposure (CHE) remains inconclusive. The aim of our study was to examine the potential association among the cecal microbiota community, physiological indicators and serum metabolite profiles in CHE hens. One hundred and eighty Hy-Line Brown hens were randomly allocated into three groups, thermoneutral control (TN), heat stress (HS) and pair-fed (PF). The experiment lasted for 5 weeks, with the first 2 weeks serving as the adaptation period. Results showed that the expression level of heat shock protein 70 (HSP70) in both serum and cecal tissues was significantly increased in HS group. Serum parameters analysis also revealed that CHE caused physiological function damage and metabolic disorders. These results suggest experiment was successful inducing chronic heat stress.16S rRNA sequencing analysis showed that the CHE can clearly induce dysbiosis of gut microbial community reflected in the increment of F/B ratio. Besides, serum untargeted metabolomics revealed the relative concentrations of 40 metabolites were significantly altered in HS group compared with the TN group. Pathway analysis showed that these metabolites were mainly involving the increased proteolysis rather than lipolysis and this tendency could be a specific metabolic adaptation of the poultry. The pair-feed experiment showed that the above changes induced by CHE were partly independent from the reduction of feed intake. Mantel correlation analysis between gut microorganisms and physiological indicators showed that the phylum Firmicutes and Euryarchaeota have a potential interaction with serum lipid parameter. Random forest analysis showed that both genus Faecalibacterium and Methanobrevibacter were important predictors of the CHE induced lipid metabolism disorder. Taken together, our findings may contribute to a better understanding of the metabolic mechanisms underlying the energy metabolism imbalance caused by the CHE and provide novel insights into the host-microbes interactions and its effects on the metabolic adaptation of hens under chronic heat exposure.